Nuclear and Radiological Data Available in the International Atomic Energy Agency (IAEA) Databases (Rudarsko-geološko-naftni zbornik, 2023)
Having access to relevant data is essential for ensuring the quality and outreach of research work. In the context of the nuclear field, access to information and data facilitates competence building, long-term professional development, research, and information dissemination. Potential users of nuclear information resources come from different domains: scientists, experts, students, and the public. One of the main roles of the International Atomic Energy Agency (IAEA) is to ensure and promote peaceful uses of atomic energy worldwide. Through their activities, the IAEA strongly encourages the exchange of scientific and technical information. This paper presents an overview of different nuclear and radiological data available in several International Atomic Energy Agency databases. All data is available free of charge for educational and informational use. A summary of information is given for each database presented on the content, access options, copyright, acknowledgement, and dissemination of the available information. A concise summary of this various data might help in capacity building, as well as encourage research and information sharing between different stakeholders in the field.